A genre analysis of online children’s book reviews / Lim Sue-Ann Esther - Lim, Sue-Ann Esther (2019)
Book reviews are assumed to be objective and unbiased, but Bhatia (2004) categorised book reviews as peripheral members of the promotional genre colony. Matson’s (2008) study revealed a promotional function in the inception of children’s book reviews, yet contemporary librarianship expects current book reviews to systematically review newly published books. As book reviews can greatly impact purchasing decisions, this research investigates the communicative purposes of online children’s book reviews (OCBR) from a genre analysis perspective. It extends the analysis of typified moves and generic structure by studying the linguistic features and visuals incorporated in the reviews. Twenty OCBR are analysed using Motta-Roth’s (1995) rhetorical structure for academic book reviews, followed by a closer analysis of the linguistic features and visuals used to realise the rhetorical structure and the genre’s communicative purposes. Findings establish a definite promotional purpose in the genre. Certain phrases in the data are indicative of a marketing strategy known as ‘Unique Selling Proposition’ (USP) and both review journals practice the awarding of a star to outstanding books, which is similar to the ‘Endorsement/Testimonials’ move in Kathpalia’s (1992) rhetorical structure for advertisements. Linguistic and visual analyses also indicate the presence of publishing discourse, promotional discourse and discourse in blurbs in OCBR.